PENGEMBANGAN VIDEO TUTORIAL PEMBUATAN SELAI PEPAYA PADA SUBMATERI PERAN TUMBUHAN DI BIDANG EKONOMI - Grace Tessalonika; Entin Daningsih; Asria Nurdini Mardiyyaningsih (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
The delivery of material in the learning process theoretically, without concrete example arounds students has not been able to increase awareness of a plant care product that will have a higher selling value. The purpose of this study is to develop a tutorial video that can describe the role of plants in the economic field and the procedure for making papaya jam as a factual example and its testing in organoleptic tests. The tutorial video is designed according to the potential and problems, data collection, product design, validation and revision which are five of the 10 stages in the Research and Development (R&D) method. Design validation consist of instrument and media validation conducted by five validators. The instrument validation includes the format, content, language evaluated by two biology education lecturers. Meanwhile, media validation consist of 11 aspects with 16 criteria conducted by to lecturers and three high school teachers using a Likert scale. Validity is calculated by the Lawshe method. The validation result show that the avarage CVR in all aspects options 1.00 which is considered valid. However, this tutorial video needs to be tested in the process of learning on the role of plants in the economy.